Subtle Influence of ACE2 Glycan Processing on SARS-CoV-2 Recognition. Issue 4 (19th February 2021) - Allen, Joel D.; Watanabe, Yasunori; Chawla, Himanshi; Newby, Maddy L.; Crispin, Max
Graphical abstract: Highlights: N-linked glycans of ACE2 have been suggested to play a role in SARS-CoV-2 binding. Using glycan engineering we generated a panel of glycan modified ACE2 variants. The binding of these variants to spike protein was determined using SPR and LC-MS. These results suggest a limited role for the glycans of ACE2 in SARS-CoV-2 binding. SARS binding with ACE2 is slightly influenced by sialylation and mannosylation. Abstract: The severity of SARS-CoV-2 infection is highly variable and yet the molecular basis for this effect remains elusive. One potential contribution are differences in the glycosylation of target human cells, particularly as SARS-CoV-2 has the capacity to bind sialic acid which is a common, and highly variable, terminal modification of glycans. The viral spike glycoprotein (S) of SARS-CoV-2 and the human cellular receptor, angiotensin-converting enzyme 2 (ACE2) are both densely glycosylated. We therefore sought to investigate whether the glycosylation state of ACE2 impacts the interaction with SARS-CoV-2 viral spike. We generated a panel of engineered ACE2 glycoforms which were analyzed by mass spectrometry to reveal the site-specific glycan modifications. We then probed the impact of ACE2 glycosylation on S binding and revealed a subtle sensitivity with hypersialylated or oligomannose-type glycans slightly impeding the interaction. In contrast, deglycosylation of ACE2 did not influence SARS-CoV-2 binding. Overall, ACE2 glycosylation does not significantly influence viral spike binding. We suggest that any role of glycosylation in the pathobiology of SARS-CoV-2 will lie beyond its immediate impact of receptor glycosylation on virus binding.